Community service in the Netherlands: its effects on recidivism and net-widening - Spaans, E. C. (International criminal justice review, 1998)
Community service was introduced in the Netherlands in 1981 in an effort to reduce the use of short-term imprisonment. Following the successful example of Great Britain, an experiment with community service for adult offenders was started in eight jurisdictions. To make sure that community service would be used as a substitute for incarceration, rules prescribed that community service could only be imposed to replace an intended unconditional prison sentence of six months or less. Sentencing people to perform unpaid work rather than spend time in prison was supposed to lower the pressure on prison capacity, save money, and have a negative effect on reoffending. Community service turned out to be a "popular" sentence. The number of community service orders (CSOs) annually imposed increased from 213 in 1981 to 12,737 in 1995. In 1989 community service became the third principal penalty under the Dutch Penal Code. Despite its popularity, however, there are strong indications that the work sentence is not always being used as an alternative to short-term incarceration but is being employed as an alternative to nonincarcerative sentences as well. Similarly, the effects of community service on reoffending are less clear than was expected. This article describes the major outcomes of recently conducted research into community service in the Netherlands. By comparing persons who received a CSO to persons who were sentenced to a short prison term, the effect of community service on recidivism and the application of the work sentence will be discussed